Nonparametric Euler equation identification and estimation - Juan Carlos Escanciano; Stefan Hoderlein; Arthur Lewbel; Oliver Linton; Sorawoot Srisuma (Centre for Microdata Methods and Practice (cemmap), 2015)
We consider nonparametric identification and estimation of pricing kernels, or equivalently of marginal utility functions up to scale, in consumption based asset pricing Euler equations. Ours is the first paper to prove nonparametric identification of Euler equations under low level conditions (without imposing functional restrictions or just assuming completeness). We also propose a novel nonparametric estimator based on our identification analysis, which combines standard kernel estimation with the computation of a matrix eigenvector problem. Our estimator avoids the ill-posed inverse issues associated with existing nonparametric instrumental variables based Euler equation estimators. We derive limiting distributions for our estimator and for relevant associated functionals. We provide a Monte Carlo analysis and an empirical application to US household-level consumption data.
Keywords: C14; D91; E21; G12; 330; Euler equations; marginal utility; pricing kernel; Fredholm equations; integral equations; nonparametric identification; asset pricing